Pengabdian Masyarakat dalam Melestarikan Kearifan Lokal: Tradisi Memelihara Laut di Desa Pelanduk Kecamatan Mandah Kabupaten Indragiri Hilir Provinsi Riau - Imratul Sa’Diah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
This research is motivated by the problem of the lack of community participation in developing marine ritual traditions, as well as the limited sources that prove the importance of the annual marine ritual. This type of research is historical research with a qualitative approach and descriptive narrative method. This research includes heuristics, source criticism, interpretation, and writing stages. Data sources used include journals discussing marine ritual traditions in Pelanduk Village, Mandah District, as well as annual observations before the month of Muharram, in-depth interviews with people in charge of marine rituals, and literature studies. The marine ritual tradition in Pelanduk Village is a cultural heritage passed down from generation to generation by coastal communities in Mandah District, Riau Province. This ritual is carried out as an expression of gratitude to God Almighty and respect for the sea as a source of life. This study aims to explore the history, implementation process, meaning, and role of marine ritual traditions in the lives of local communities. The results show that marine rituals contain strong spiritual, social, and ecological values. This ritual involves various cultural symbols, such as offerings, collective prayers, and traditional ceremonies that reflect the harmonious relationship between humans and nature. This study concludes that sea rituals are a cultural heritage that strengthens the identity of coastal communities.